Postprandial response of bone turnover markers in patients with Crohn’s disease - Karatzoglou, Ioannis (Baishideng Publishing Group Inc, 2014)
AIM: To investigate the postprandial response of bone turnover markers in patients with Crohn’s disease (CD). METHODS: Fifty nine patients with CD aged 38 ± 14 years, and 45 healthy individuals matched for age and body mass index were included in the study. All participants underwent an oral glucose tolerance test (OGTT) after an overnight fast and serum levels of the bone resorption marker C-terminal crosslinking telopeptide of type I collagen (CTX-I) and the bone formation marker procollagen type I N propeptide were measured. Activity of the disease was assessed by calculation of the Crohn’s disease activity index (CDAI). RESULTS: Serum CTX-I was significantly higher in patients compared to controls (CTX-I: 453 ± 21 pg/mL vs 365 ± 25 pg/mL, P = 0.008), and values were significantly correlated with the activity of the disease (r = 0.435, P = 0.001). Results from OGTT-induced suppression of CTX-I showed two different trends. Patients with more active disease (assessed as CDAI > 150) had a more excessive suppression of CTX-I compared to controls (55% vs 43% P < 0.001), while patients on remission (assessed as CDAI < 150) demonstrated an attenuated CTX-I suppression (30% vs 43% P < 0.001). In line with this, CTX-I suppression after oral glucose load was significantly correlated with the activity of the disease (r = 0.913, P < 0.001). CONCLUSION: The physiological skeletal response of postprandial suppression of bone resorption is maintained in patients with CD and is strongly dependent to the activity of the disease.